Grasi dalam Perspektif Hukum Islam dan Hukum Positif Indonesia - Imdadurrouf, Imdadurrouf (Fakultas Syariah IAIN Purwokerto, 2010)
As one of the rights owned by the president, clemency is controlled by the Indonesian Constitution, UUD 1945. In Islamic law there is also a possibility to forgive one’s mistake in the name of justice and truthful.